Os Microplanos de Montez Magno e os infra-minces de Duchamp: a hipersensível vastidão de um ínfimo intervalo - Gouveia, Ana Elisabete de (2012)
This study presents an analysis of the series Microplanos whose author is the Pernambuco born artist Montez Magno, discusses the central propositions created by the artist , that focuses in the notion of the Infra-mince , Term created but never revealed except through samples by Marcel Duchamp to designate certain fundamental operations in the body of his works. The research enters by an investigacion of the notion of the infra-mince under the light of the metafenomenologia of the portuguese filosopher José Gil and raises some questions of its possible influence of this term in other segments of art and science.